“The Sea… Their Life Line: The human ecology of the Chinese fishermen of Pasir Penambang, off Kuala Selangor, West Malaysia / D. Gerardine Mrie - D. Gerardine , Mrie (1979)
This is an exploratory study of the human ecology of the Chinese fishermen of Pasir Penambang, off Kuala Selangor, West Malaysia. The author first briefly discusses the various existing literature on the ecology of fishermen in Malaysia. The scope of study and methodology exployed is also dealt with. The bulk of the study deals with the structure functions of the fishing industry in Pasir Penambang and the impact of development and modernization on the lives of the Chinese fishermen in Pasir Penambang.